App-Tailoring Requirements to Increase Stress Management Competencies Within Families: Cross-sectional Survey Study - Laura Luise Bischoff; Hannes Baumann; Charlotte Meixner; Patricia Nixon; Bettina Wollesen (JMIR Publications, 2021)
BackgroundFamilies experiencing high levels of psychological distress are considered a particularly vulnerable population for adverse effects on mental and physical health. Moreover, highly stressed individuals engage less in mental health promoting activities and show low stress management competencies. App-based stress interventions seem promising for the treatment and prevention of stress outcomes and might be a low-threshold solution. ObjectiveThe aim of this study was to identify the requirements for a tailored app to reduce stress in a cohort of highly stressed families that have low stress management skills. MethodsParents (n=1008; age: mean 47.7 years, SD 6.1; female: 599/1008, 59.7%) completed an extensive web-based survey and were subdivided into a target (stressed individuals with low stress competency) and nontarget group according to their reported stress level and stress management competencies. Group differences were analyzed using analysis of variance. In principal component analysis with Kaiser varimax rotation, personally defined stress management goals were grouped into components. Linear regression models were also calculated. ResultsA 3-factor solution cumulatively explained 56% of the variance in personally defined goals of interest for stress management with (1) active strategies (25.61% explained variance), (2) general competency (17.95% explained variance) and (3) passive strategies (12.45% explained variance). The groups differed in age (F1,978=27.67, P<.001), health index (F1,958=246.14, P<.001), personally defined general-competency goal (F1,958=94.16 P<.001), as well as "information acquisition" (F1,971=14.75, P<.001) and "need for stimulation" (F1,981=54.49, P<.001) personality traits. A regression model showed that for the active strategies goals of interest, only app feature information or instructional videos had a significant effect (P=.02). The general competency factor showed none, and the passive strategies factor showed significant effects for 2 app features-suggestions for planning possible activities with the family (P=.01) and diaries for documentation and development of strategies (P=.03). ConclusionsThe results of this survey study highlight the need to develop an app to increase stress management competencies that takes into consideration perceived stress level, stress management skills, personality, and personally defined goals of the user. The content of the app should be tailored to previously detected personality traits, especially selective information acquisition and low need for stimulation. Furthermore, personally defined stress management goals seem to affect interest in some features.